2018
DOI: 10.1051/e3sconf/20184400171
|View full text |Cite
|
Sign up to set email alerts
|

Indoor air quality modelling and measurements of a studio apartment with a mechanical exhaust system

Abstract: Abstract. The aim of the research were measurements and an attempt to model the indoor air quality (IAQ) within a studio apartment with a mechanical exhaust system, manually controlled by the occupants. The authors based the modelling on the occupancy schedule of the family members and the recorded operation duration of the ventilation system. The purpose of the performed analysis was to answer the question if it is possible and to what extent to reflect numerically the conditions within the tested object. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…The study found that CO 2 concentrations frequently exceeded recommended levels. The numerical simulations demonstrated a strong correlation with actual measurements, validating their accuracy in predicting indoor air quality [21].…”
Section: Introductionsupporting
confidence: 54%
“…The study found that CO 2 concentrations frequently exceeded recommended levels. The numerical simulations demonstrated a strong correlation with actual measurements, validating their accuracy in predicting indoor air quality [21].…”
Section: Introductionsupporting
confidence: 54%
“…Some studies have been performed to calculate hourly volumes of outdoor air on generic control volumes, but they did not consider real building structures and spaces [27,28]. In [29], the indoor air quality (IAQ) was modelled within a studio apartment with a mechanical exhaust system that was manually controlled by the building occupants. In [30], the effectiveness of an air terminal device with a changing geometry was verified in terms of improvement in indoor air quality.…”
Section: Introductionmentioning
confidence: 99%
“…Despite being useful for design optimization, the installation of wind tunnels is expensive and time-consuming [20,21]. Therefore, numerical models and simulations such as CFD for wind patterns or CONTAM for interior air quality are frequently employed due to their thorough, precise, and cost-effective nature, particularly in the context of buildings [5,22]. However, certain guidelines should be followed to ensure the accuracy and precision of these results.…”
Section: Introductionmentioning
confidence: 99%